Implementasi Sistem Informasi Geografis untuk Optimalisasi Pemantauan P2TL: (Studi Kasus di Kabupaten Nabire, Papua Tengah) - Arief Rahman Hakim; Karjo Padondan (Jurnal Teknologi dan Informatika, 2026)
Electricity Usage Control (P2TL) is a strategic program of PT PLN to reduce losses due to illegal electricity usage. This study aims to analyze the use of Geographic Information Systems (GIS) based on QGIS in supporting P2TL monitoring in Nabire Regency. The data used includes 54,939 customer coordinate points, collected through field surveys using GPS with a high level of accuracy. The method applied is descriptive spatial analysis with overlay techniques and spatial clustering. The results of the study show an uneven distribution of customers between districts, with the highest concentration in Nabire District (18,247 customers or 33.2%). The dominant tariff type is R1T (60.3%) with the largest power capacity of 1300 VA (49.5%). Spatial analysis identified 12 hotspots and 8 priority monitoring zones. The application of GIS increases the effectiveness of identifying vulnerable areas by 78% and reduces the duration of field inspections by 45%. The resulting thematic map visualization provides significant support in location-based decision making.